1973
DOI: 10.1016/0022-2836(73)90272-6
|View full text |Cite
|
Sign up to set email alerts
|

Metastable secondary structures in ribosomal RNA molecular hysteresis in the acid-base titration of Escherichia coli ribosomal RNA

Abstract: The metastable conformational states which underlie the hysteresis displayed by Escherichia coli ribosomal RNA in its pH titration in the acid range have been analyzed in terms of acid-stable RNA secondary structures. Sedimentation measurements show that the phenomenon is ktramolecular, so that analysis of the hysteresis loops can, in principle, reveal details of molecular architecture. Hysteresis cycles obtained spectrophotometrically and potentiometrically were compared for RNA in solutions of different ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…A possible interpretation of this phenomenon, especially in relation to the results discussed in the previous section, is that base-paired regions persist at pH 3 and high ionic strength, preventing complete condensation of the molecule. This is consistent with the proposal of Rezvin et al (1973) that metastable base-paired regions are formed under these conditions.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…A possible interpretation of this phenomenon, especially in relation to the results discussed in the previous section, is that base-paired regions persist at pH 3 and high ionic strength, preventing complete condensation of the molecule. This is consistent with the proposal of Rezvin et al (1973) that metastable base-paired regions are formed under these conditions.…”
Section: Resultssupporting
confidence: 93%
“…Indeed, Watson and Kidson (1969) have summarized the factors which appear to affect RNA tertiary structure: influence of cation concentration upon base stacking, intrachain electrostatic repulsion due to partially charged phosphate groups, and variable extents of base pairing. To these should probably be added the possible formation, at low pH, of metastable base-paired regions involving guanine residues (Rezvin et al, 1973). The results obtained here lead us to conclude that these influences result in several discrete configurations.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It will be of particular interest to observe the extent of variation in that region as further threedimensional structures are obtained for tRNA, especially if changes are observed under different crystallization conditions. Structural changes dependent on pH are known in protein crystallography (Vandlen and Tulinsky, 1973;Mavridis et al, 1974), and they can be inferred to occur in other RNAs from the hysteresis observed in acid-base titrations of RNA (Revzin et al, 1973).…”
Section: Discussionmentioning
confidence: 99%